Analysis of the Influence of Liquidity and Solvency on the Profitability of PT Bank Mandiri (Persero) Tbk - Lisi Rahmadayanti; Yun Fitriano; Abdul Rahman (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
This study aims to analyze the effect of liquidity (LDR) and solvency (CAR) on profitability BOPO. This analysis uses the independent variables of liquidity, solvency. The independent variable is focused on LDR, CAR while the dependent variable is profitability, namely BOPO. The data used is secondary data originating from the annual financial statements of independent banks listed on the Indonesian stock exchange for the period 2010 to 2020. The data testing method uses the classical assumption test, multiple linear regression, coefficient of determination (R2), by testing the hypothesis test. t and f test. The results of the study using multiple linear regression with t-test showed that LDR had a t-count value of 2.520 with a significant level of 0.03 more than 0.05 or 5%. The CAR has a t-count of 5.170 with a significant level of 0.016 which is greater than 0.05 or 5%. Based on the results of the f (simultaneous) test, it shows that the calculated f value is 9.929 with a significant level of 0.023 which is smaller than 0.05 or 5%. Thus, LDR, CAR have a positive and significant effect on BOPO